ANALISIS PENGENDALIAN KUALITAS PRODUK PLASTIK DI PT. YEAKIN PLASTIC INDUSTRY - Ardianto, Septian Faris; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2023)
In an increasingly advanced age, All kinds of work and ways change very quickly every year. oth in the field of service and manufacturing. Pt yeakin plastic industry has 3 lines one of which is plastic production, in the manufacture of its own plastic products, pt yeakin plasticindustry batam only production material that has become plastic roll into plastic polybag based on the results of observational research in the field, in finding problems in the quality of the product and in finding various defects in the product that cause the quality of plastic to be decreased and not in accordance with the standard. Procedures based on standards set by the company, the company sets its own target of a maximum of 5% of total production in the production process.the purpose of this study is to identify the level of variation in defects in the plastic production process, triggering the types of defects that occur in plastic during the cutting process at PT Yeakin Plastic Industry Batam